(untitled) (International Journal of Studies in Nursing, 2017)
Background: The term sarcopenia includes the involuntary loss of muscle mass that occurs during the aging process beginning in middle adulthood. Case Presentation: We present a case study that was used to determine the effectiveness of a 12 week resistance training (RT) intervention to enhance overall function in an adult classified as experiencing sarcopenia. The purpose of this investigation was to determine what benefits as measured by increases in muscular fitness objectives and skeletal muscle mass index a progressive RT program might provide a very old adult. Conclusions: The subject experienced gains in upper and lower extremity strength as measured by 1RM testing. The Skeletal Mass Index (SMI) the outcome measure to determine sarcopenia showed clinical findings indicating that the subject was no longer classified as sarcopenic. The present study results also suggest that a progressive RT program is safe and effective for yielding strength gains in a very old individual.